Effect of the SWOM strategy on kinetic flexibility and volleyball block accuracy in students of Physical Education and Sports - Dahash , Muthana Ab.; Ibrahim , Firas S.; Salman , Maher Ab. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of the present study was to identify the effect of the S.W.O.M. strategy in developing the flexibility and skill of the volleyball block for students. The present study was conducted on the volleyball players of the 3rd stage of the College of Physical Education and Sports Sciences of the University of Kufa, within the time frame of March 2021 to July 2021. The present study had an experimental design. The College of Physical Education and Sports Sciences of the University of Kufa was identified as the research community for the current study. A total of 28 students were recruited as participants for the present study. Participants were allocated into two groups (experimental group and control group), by simple random allocation method (raffle). The participants of the experimental group were directed as per the weekly plans and the S.W.O.M. strategy, at the rate of one teaching class per week. However, the participants of the control group were provided with the training based on their regular adopted strategy, prepared by the trainer. Based on the findings of the present study, the researchers concluded that the S.W.O.M. strategy significantly aided in improving the agility of students along with improvement in the block skills of the players.